2020
DOI: 10.3389/fnmol.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

Canine Adenovirus 2: A Natural Choice for Brain Circuit Dissection

Abstract: Canine adenovirus-2 (CAV) is a canine pathogen that has been used in a variety of applications, from vaccines against more infectious strains of CAV to treatments for neurological disorders. With recent engineering, CAV has become a natural choice for neuroscientists dissecting the connectivity and function of brain circuits. Specifically, as a reliable genetic vector with minimal immunogenic and cytotoxic reactivity, CAV has been used for the retrograde transduction of various types of projection neurons. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 112 publications
1
8
0
Order By: Relevance
“…Consistent with the current work, a study investigating self-stimulation of dopamine terminals in NAc found that mice were flexible following reversal of the active nosepoke (Zell et al, 2020). Future work could explore the difference between stimulating cell bodies and terminals by employing retrograde tracing and intersectional approaches, including Canine adenovirus-2 (Lavoie & Liu, 2020), to perform optogenetics specifically targeting distinct dopamine projection populations (Lerner et al, 2015).…”
Section: The Role Of Dopamine In Reversal Learningsupporting
confidence: 78%
“…Consistent with the current work, a study investigating self-stimulation of dopamine terminals in NAc found that mice were flexible following reversal of the active nosepoke (Zell et al, 2020). Future work could explore the difference between stimulating cell bodies and terminals by employing retrograde tracing and intersectional approaches, including Canine adenovirus-2 (Lavoie & Liu, 2020), to perform optogenetics specifically targeting distinct dopamine projection populations (Lerner et al, 2015).…”
Section: The Role Of Dopamine In Reversal Learningsupporting
confidence: 78%
“…Consequently, the specificity of PRS×8 driven expression can likely be improved by using lower titers in the future. However, it is important to note that all these studies used PRS×8-controlled constructs in combination with recombinant adenoviruses 21 or canine adenovirus 2 (CAV-2) [22][23][24]36 , which have a different tropism than rAAV2/9 used in our study 41 . With respect to rAAVs, insufficient PRS×8 mediated transgene expression was reported with rAAV2/7 42 (~20.6 % efficacy), while robust expression was reported upon injection of rAAV2/9 35,43 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 0.25–0.5 µL of CAV2 spread on average by 200 µm from the center of the injection site, while 0.25 µL of rAAV2-retro spread four times more [ 3 , 54 ]. More restricted diffusion of CAV2 has been proved useful when studying small brain structures [ 55 ]. Whereas AAVs transduce neuron soma to express gene transcripts, CARs are predominantly located on the axon surface [ 29 ] making CAV2-based vectors more suitable for the retrograde transduction of selected neuron populations both in the forebrain and spinal cord [ 28 , 30 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas AAVs transduce neuron soma to express gene transcripts, CARs are predominantly located on the axon surface [ 29 ] making CAV2-based vectors more suitable for the retrograde transduction of selected neuron populations both in the forebrain and spinal cord [ 28 , 30 , 56 ]. At the same time, it has been shown that CAV2 transduction is limited to some types of neurons or pathways [ 55 ], possibly due to the varying expression level of CARs in different neuron populations [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%